Stratification of chlorinated ethenes natural attenuation in an alluvial aquifer assessed by hydrochemical and biomolecular tools - Němeček, Jan; Dolinová, Iva; Macháčková, Jiřina; Špánek, Roman; Ševců, Alena; Lederer, Tomáš; Černík, Miroslav (Chemosphere, 2017)
Biomolecular and hydrochemical tools were used to evaluate natural attenuation of chlorinated ethenes in a Quaternary alluvial aquifer located close to a historical source of large-scale tetrachloroethylene (PCE) contamination. Distinct stratification of redox zones was observed, despite the aquifer's small thickness (2.8 m). The uppermost zone of the target aquifer was characterised by oxygen- and nitrate-reducing conditions, with mixed iron- to sulphate-reducing conditions dominant in the lower zone, along with indications of methanogenesis. Natural attenuation of PCE was strongly influenced by redox heterogeneity, while higher levels of PCE degradation coincided with iron- to sulphate reducing conditions. Next generation sequencing of the middle and/or lower zones identified anaerobic bacteria (Firmicutes, Chloroflexi, Actinobacteria and Bacteroidetes) associated with reductive dechlorination. The relative abundance of dechlorinators (Dehalococcoides mccartyi, Dehalobacter sp.) identified by real-time PCR in soil from the lower levels supports the hypothesis that there is a significant potential for reductive dechlorination of PCE. Local conditions were insufficiently reducing for rapid complete dechlorination of PCE to harmless ethene. For reliable assessment of natural attenuation, or when designing monitoring or remedial systems, vertical stratification of key biological and hydrochemical markers should be analysed as standard, even in shallow aquifers.
Keywords: Indigenous microorganisms; biodegradace; chemické látky znečišťující vodu; Chloroflexi; halogenace; železo; Water Pollutants, Chemical; monitorování životního prostředí; High-Throughput Nucleotide Sequencing; Halogenation; podzemní voda; Chlorinated solvents; Hydrochemical markers; Ethylenes; Biological markers; Groundwater; Iron; vysoce účinné nukleotidové sekvenování; Environmental Monitoring; ethyleny; Natural attenuation; Biodegradation, Environmental; tetrachlorethylen; Tetrachloroethylene